100 years in retrospect articulations of Philippine identity in the undergraduate programs of the U.P. College of Music (1916 to 2016) - Carranza, Anna Patricia Rodriguez (Diliman, Quezon City U.P. College of Music, 2020)
"This thesis aims to demonstrate an analysis of the undergraduate programs of the UP College of Music from 1916 to 2016 in relation to a section of the University's purposes as stated in the UP Chapter: "(to) provide opportunities for training and learning in leadership, responsible citizenship, and the development of democratic values, institutions, and practice through academic and non-academic programs, including sports and enhancement of nationalism and national identity." This study aims to make a historiography of music education and Philippine identity through an analysis of: 1) U.P. College of Music undergraduate curricula and other related documents, 2) U.P. College of Music exit requirements, and 3) interview of key people instrumental to the institution of these programs. Data was gathered from official documents pertaining to the College's undergraduate programs, exit requirements, and interview of deans and other pertinent persons. The study reveals that the undergraduate curricula of the U.P. College of Music have espoused four different ideas of Philippine identity, as represented by four periods, namely: Assimilation of Foreign Influence (1916 to 1946), Reflections of Asianization (1947 to 1968), Streamlining vis a vis Indigenization (1969 to 1999), and Re-evaluation and Multiplicity (2000 to 2016).
Thesis
Keywords: Nationalism -- Philippines